THE EFFECT OF USING DIGITAL FLASHCARDS ON WORDWALL TOWARDS THE STUDENTS’ VOCABULARY MASTERY AT THE 7TH GRADE OF ISLAMIC JUNIOR HIGH SCHOOL SEJAHTERA BADAS - Yasminto, Muhammad; Ningsih, Agustina Putri (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2024)
This study aims to know the effect of digital flashcard media on wordwall app on students’ vocabulary mastery at the 7th grade of Islamic Junior High School Sejahtera Badas 2023/2024. This research used quantitative research and design used is a pre-experimental design with one experimental group only. The researchers used Digital Flashcards as a learning media and iwritten test used as an instrument. The population of this research is 7th grade students with 26 students divided into two classes. The sample technique used Saturated Sampling technique consisting of 13 students in which they were taken from the boarding school class. The findings show that there is a significant difference between the results of the pretest and posttest. The mean score of post-test is higher than pre- test (91,69 >60,61). The result of this research was obtained from calculating data using wilcoxon test with the a significance value of 0.002 (<0.05). It proved that the alternatives hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Thus it can be said that there is a difference in the value of students' vocabulary mastery between before and after treatment. In other words, using Digital Flashcards on students' vocabulary mastery is effective